2007
DOI: 10.1063/1.2816439
|View full text |Cite
|
Sign up to set email alerts
|

Isochoric heating in heterogeneous solid targets with ultrashort laser pulses

Abstract: We study ultrafast heating of thin plastic foils by intense laser irradiation theoretically using collisional two-dimensional particle-in-cell simulations. We find that the laser-generated hot electrons are confined laterally by self-generated resistive magnetic fields, heating the laser focal area beyond keV electron temperatures isochorically in a few picoseconds. Using this confinement one can excite shock waves that compress the plasma beyond solid density and achieve keV thermal plasmas before the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…1. Experiments and simulations have shown that it is possible to isochorically heat targets at solidstate density to temperatures of a few hundred eV or even a few keV [60][61][62]. Since in this regime the heating of the target is mainly conducted by secondary parti- cles, i.e., hot electrons generated in the laser-target interaction, a more sophisticated model is necessary compared to the low-density case.…”
Section: W/cmmentioning
confidence: 99%
“…1. Experiments and simulations have shown that it is possible to isochorically heat targets at solidstate density to temperatures of a few hundred eV or even a few keV [60][61][62]. Since in this regime the heating of the target is mainly conducted by secondary parti- cles, i.e., hot electrons generated in the laser-target interaction, a more sophisticated model is necessary compared to the low-density case.…”
Section: W/cmmentioning
confidence: 99%
“…This situation has previously been considered in terms of guiding and collimating the fast electrons, however the heating of the wire itself was not considered in much detail, nor was a more realistic fast electron divergence used in these previous studies. Some attention has been given to target heating for driving hydrodynamics by Sentoku and co-workers 13 , although this did not use resistive guiding as such and considered relatively thin targets. Hence the need to revisit this scenario in order to more properly assess the simple wire as a route to launching strong cylindrical shocks into dense material.…”
Section: Introductionmentioning
confidence: 99%
“…Because the new target shape proposed here has not been fabricated yet, we used the two-dimensional (2D) particlein-cell (PIC) code PICLS (Sentoku et al, 2007) to run collisionless simulations and assess the electro-magnetic fields structures and proton beam characteristics in comparison with flat targets. We ran several intensities to span the range available to short pulse lasers.…”
Section: A New Shape For Particle Beam Generationmentioning
confidence: 99%